Prevalence of jaw lesions in Bagalkot population a clinical and radiographic study - Dantu, Raghunath; Puranik, Surekha R. (International Journal Of Community Medicine And Public Health, 2017)
Background: Objective of the study was to estimate the prevalence of the various jaw diseases/ pathology in a group of North Karnataka population. Jaw lesions will be further clinically assessed and investigated (radiographs, advanced imaging modalities and laboratory investigations). Methods: During the investigation, 3500 patients attending the oral medicine department of P.M.N.M Dental College and Hospital for a period of 15 months were examined for the presence of jaw lesions. The population of this study consisted of males and females of all age groups. All the subjects were examined, diagnosed and referred to the appropriate department for dental treatment. Results: Of 3500 patients screened, 1072 patients had lesions. Out of these, 567 were males and 505 were females. The most commonly found lesion was periapical abscess followed by localized periodontitis, Generalized periodontitis, periapical granuloma, Radicular cyst with least being malignant lesions and bone tumours. Conclusions: This prevalence study in a dental institute showed lack of oral health \ awareness among the patients and calls for the importance of the role of dentist in educating the patients regarding maintenance of oral health and also the urgent need for treatment.